Logistics regression analysis of teacher perceptions on the implementation of school based assessment in teaching mathematic - Mohamad Radzi, Farhana; Md Sawari, Siti Salwa (Scholars Middle East Publishers, 2018)
Over the years, the issue of SBA in Malaysia continues to gain attention. The issue that highlighted in this study is the reliability and validity of SBA as an assessment system. It is an unquestionable fact that teachers are given power to assess their students; however, due to lack of information, training, materials, guidelines and infrastructure in executing the SBA, it has led to a subjective evaluation. Thus this article intend to examine teachers‟ perception on the effectiveness of SBA practiced in secondary schools. The researcher investigated teachers‟ perceptions of the role of SBA in teaching and learning mathematics. The nature of the study will be a quantitative approach. A questionnaire with three different parts was designed to collect the data. The descriptive statistics, logistic regression analysis and Pearson correlation were used to answer all respective research questions in this quantitative study. Results and findings led to the conclusion that the teachers who responded “SBA is effective” have a higher probability to have a positive perception on the students‟ achievement in Mathematics